Enhanced inter‐lighting interference cancellation using power control to improve the performance of indoor visible light communication systems. Issue 6 (1st December 2018) - Romero‐Munoz, Gabriela Alejandra; Kim, Kyuntak; Lee, Kyesan
Abstract : In this study, the authors propose an enhanced inter‐lighting interference cancellation (E‐ILIC) in order to distinguish the received signals, combating the equal powers at the receiver side and hence improve the average bit error rate (BER) performance of a multiple‐input‐single‐output visible light communication (VLC) system. VLC is a promising technology for indoor environments, it makes use of the light emitting diode (LED) lamps already installed to transmit information through the visible light. When several LEDs transmit simultaneously different data to increase the transmission capacity, it leads to co‐channel interference that degrades the BER performance. For this reason, they investigate E‐ILIC that is a combination of ILIC with closed loop power control to receive the signals with different power level. It employs power allocation at the transmitter when the received power ratio does not comply with a specific threshold. Furthermore, it reduces significantly the interference between adjacent LED lamps, obtaining useful information at the receiver side. Through computer simulations, E‐ILIC achieves the best average BER performance in any user position when the assignment of the power weights is correctly performed on the LEDs.